Rhythmic Gymnastics Activities on Gross Motor Development in Early Childhood - Atirah Ahdal; Herlina Herlina; Herman Herman; Wahira Wahira; Surya (PT. Riset Press International, 2026)
Early childhood gross motor development is crucial to support physical activity, coordination, and independence, as stipulated in Law No. 20 of 2003 concerning the National Education System, which emphasizes physical stimulation from an early age. Early observations showed a lack of structured activities, such as rhythmic gymnastics, in early childhood education, leading to gross motor delays in skills like jumping and running, even though conventional activities were available. Rhythmic gymnastics, with musical accompaniment and rhythmic movements, is considered effective in stimulating large muscles based on the theories of Gallahue and Ozmun. The study aims to test the effectiveness of rhythmic gymnastics with the theme